The Degree of Canning Islamic Education for the Secondary Stage in the Twenty-First Century from the Point of View of the Subject Teachers - Hamdan, Iyad Sa’ed; Al-Tous, Dania Ali (Journal of Educational and Psychological Sciences, 2022)
The study aimed to ascertain the degree to which Islamic education books for the secondary stage included twenty-first-century skills, as perceived by subject teachers. The descriptive survey method was used in the study, and the study members were chosen at random stratified from teachers of Islamic education in government schools affiliated with the Directorate of Education in Marka District, with a sample size of 95 male and female teachers. The research tool was a questionnaire with 26 indicators distributed on four twenty-first century skills (creativity, critical thinking, problem solving, communication, and cooperation). The tool’s validity and dependability have been confirmed. The study’s findings revealed that the degree of inclusion of twenty-first-century skills in Islamic education books for the secondary stage was high. The creativity skill came first, followed by the communication skill, followed by the critical thinking skill, problem solving, and finally the cooperation skill. The findings also revealed statistically significant differences at the significance level (a = 0.05) in the responses of the study sample members on the extent to which Islamic education books for the secondary stage included the skills of The variables of gender and academic qualification are attributed to the twenty-first century, while there are no statistically significant differences in the responses of the study sample members to the degree of inclusion of twenty-first century skills in Islamic education books for the secondary stage due to the experience variable.